2021
DOI: 10.1001/jamanetworkopen.2021.39585
|View full text |Cite
|
Sign up to set email alerts
|

Variation in State-Level Eviction Moratorium Protections and Mental Health Among US Adults During the COVID-19 Pandemic

Abstract: IMPORTANCEAlthough evictions have been associated with adverse mental health outcomes, it remains unclear which stages of the eviction process are associated with mental distress among renters. Variation in COVID-19 pandemic eviction protections across US states enables identification of intervention targets within the eviction process to improve renters' mental health. OBJECTIVETo measure the association between the strength of eviction protections (ie, stages blocked by eviction moratoriums) and mental distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…After screening 2294 titles, 243 abstracts, and 81 full texts, 26 articles met criteria for inclusion ( Figure 2 ), comprising 3 RCTs described in 6 articles 32 , 33 , 34 , 35 , 36 , 37 and 20 observational studies (16 longitudinal designs 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 and 4 cross-sectional quasi–waiting list control designs comparing current vs future recipients of an intervention 54 , 55 , 56 , 57 ) ( Figure 3 ; eTable 1 in the Supplement ). Most studies selected participants based on medical or social vulnerability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening 2294 titles, 243 abstracts, and 81 full texts, 26 articles met criteria for inclusion ( Figure 2 ), comprising 3 RCTs described in 6 articles 32 , 33 , 34 , 35 , 36 , 37 and 20 observational studies (16 longitudinal designs 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 and 4 cross-sectional quasi–waiting list control designs comparing current vs future recipients of an intervention 54 , 55 , 56 , 57 ) ( Figure 3 ; eTable 1 in the Supplement ). Most studies selected participants based on medical or social vulnerability.…”
Section: Resultsmentioning
confidence: 99%
“…especially for the Hispanic subgroup, 42 whereas another found that eviction moratoriums were associated with reduced anxiety and depression symptoms for Black subpopulations only. 41…”
Section: Eviction Moratoriumsmentioning
confidence: 95%
See 1 more Smart Citation
“…Further research into the health impacts and racial/ethnic disparities of COVID-19-related housing insecurity and the formulation of effective interventions and countermeasures to reduce housing insecurity effects on health outcomes, therefore, becomes critical. Research by Fenelon et al (2017) and Keene et al (2020) has indicated housing assistance is associated with improved reported health among low-income adults ( Lawler, 2001 ); and eviction moratoriums instated during the COVID-19 pandemic were also associated with better health among U.S. adults ( Leifheit et al, 2021 ). However, our research signals that, in the aftermath of acute economic events such as the current pandemic or economic recessions, these housing supports and benefits (i.e., more affordable housing, preventing insecurity in the first place) should be extended to midlife adults, particularly in Black communities, rather than only the elderly population to protect/preserve population health.…”
Section: Discussionmentioning
confidence: 99%
“…Our database documents the dates that forty-three US states and DC instituted and lifted eviction moratoria. These data were analyzed to demonstrate the associations between eviction moratoria and COVID-19 incidence and mortality [ 23 ], mental health outcomes [ 24 ], and eviction filing rates [ 25 ].…”
Section: Introductionmentioning
confidence: 99%